The Concept of Morality in Tafsir Ruh al-Ma'ani: A Thematic Study of Morality Verses - Muchammad Abdul Chalim; Putri Ayu (CV. Doki Course and Training, 2025)
This article aims to explore the concept of morality in al-Alusi's Tafsir Ruh al-Ma'ani, focusing on verses dealing with morality in the Qur'an. The research seeks to identify the ethical principles conveyed in Tafsir Ruh al-Ma’ani as well as how al-Alusi interprets moral values for individual and social life. The method used is a thematic study with a qualitative-descriptive approach, where verses about morality are analyzed based on al-Alusi's interpretation in Ruh al-Ma'ani. The results show that Tafsir Ruh al-Ma’ani presents an in-depth understanding of Islamic ethics, focusing on the development of individual morals and their influence on social relations. It emphasizes the importance of traits such as honesty, justice, patience, and compassion in achieving a harmonious life according to Islamic teachings. Morality values in the Qur'an are not only normative rules, but also contain wisdom that shapes human character towards moral perfection. Tafsir al-Alusi emphasizes the importance of moral integration in daily life as a tangible manifestation of faith. These findings contribute to enriching the understanding of the concept of morality in Islam and its relevance in the modern context.